METAVERSE: ENSURING LEGAL RECOGNITION OF AVATARS AND ELECTRONIC PERSONALITIES THROUGH A CROSS-BORDER PERSONALIZED ID-CODE - Kostenko Oleksii,; Dniprov Oleksii,; Zhuravlov Dmytro, (International Journal of Innovative Technologies in Social Science, 2024)
The study examines the topical issue of legal recognition of avatars, electronic personalities, and electronic humanoids in the context of the rapid development of digital technologies, in particular in the Metaverse ecosystem. The author emphasizes the need to reform existing and create new legal norms adapted to the digital era that would regulate the ownership and intellectual property rights to digital objects in the Metaverse, considering the global nature of digital transformations and the need for cross-border legal regulation and interaction of different legal systems to create international standards for the regulation of virtual worlds. The author proposes an innovative approach to solving these problems using blockchain technologies to create unified technological solutions that will allow for the end-to-end application of procedures for crossborder electronic identification of avatars, electronic personalities, and electronic humanoids. This will enable each avatar to have its own unique identification set of attributes, ensuring their unique and unrepeatable identification in the digital space, and will also facilitate international recognition of ownership rights to avatars, e-personalities and e-humanoids.